Ethiopia Mining Sector Development : Policy and Legislative Options Report - World Bank (World Bank, Washington, DC, 2016)
Ethiopia has many advantages as a destination for mining investment. These include promising geology, a well-designed fiscal regime, stable government and a growing domestic market. Additionally, it has a well-managed and successful artisanal and small scale mining sector. Under the second phase of Ethiopia’s Growth and Transformation Plan, Ethiopia has the ambitious target for the mining sector to contribute 10% of GDP by 2025. Ethiopia must overcome significant challenges to achieve this target. These challenges range across simplifying the licensing regime, developing its investment promotion efforts and clarifying institutional responsibilities for social and environmental management to enhancing stakeholder engagement in the governance of the sector.